Electrolyte for Aluminum Rechargeable Batteries Using Dimethyl Sulfone and Aluminum Chloride - Masanobu CHIKU; Takumi MIYAKE; Hikaru KAMEI; Eiji HIGUCHI; Hiroshi INOUE (Electrochemistry)
The electrochemical deposition and dissolution of Al with an electrolyte solution containing dimethyl sulfone and aluminum chloride was investigated at 30 °C to determine the reversibility of the process. Although aluminum deposition was observed in the electrolyte solution containing dimethyl sulfone and aluminum chloride, multiple oxidation peaks were observed in the dissolution reaction. The morphology of the deposited aluminum was observed using a scanning electron microscope, and it was found that the shape of the aluminum deposits varied greatly depending on the deposition potential. Electrochemical measurements under various conditions revealed that the oxidative decomposition of the electrolyte at the Al counter electrode during the aluminum deposition on the working electrode resulted in a large amount of aluminum oxide contamination in the deposited aluminum. To prevent such a reaction, we designed a cell in which the potential of the counter electrode did not exceed the electrochemical potential window and observed a very reversible aluminum deposition dissolution reaction. Finally, we successfully charged/discharged the Al negative electrode using a dimethyl sulfone-based electrolyte. These findings are important because the electrolytes with dimethyl sulfone and aluminum chloride are compatible as electrolytes for rechargeable aluminum batteries and because they highlight the precautions that need to be taken in their application.